2007
DOI: 10.1080/01421590701362492
|View full text |Cite
|
Sign up to set email alerts
|

A practical assessment of physician biopsychosocial performance

Abstract: Background: A biopsychosocial approach to care seems to improve patient satisfaction and health outcomes. Nevertheless, this approach is not widely practiced, possibly because its precepts have not been translated into observable skills. Aim: To identify the skill components of a biopsychosocial consultation and develop an tool for their evaluation. Methods: We approached three e-mail discussion groups of family physicians and pooled their responses to the question ''what types of observed physician behavior w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Emphasis on the doctor–patient relationship was prominent within whole person and holistic literature 14 16 27 29 30 32 35 38 39 42 45 48 50 52 54 55 57 66 67 69. Literature on the biopsychosocial approach was mixed, with the doctor–patient relationship emphasised in papers that specifically focused on the practical application of a biopsychosocial approach 46 61 65. An alternative view also existed, that considered the biopsychosocial model an ethically neutral scientific theory rather than an approach to care 41…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emphasis on the doctor–patient relationship was prominent within whole person and holistic literature 14 16 27 29 30 32 35 38 39 42 45 48 50 52 54 55 57 66 67 69. Literature on the biopsychosocial approach was mixed, with the doctor–patient relationship emphasised in papers that specifically focused on the practical application of a biopsychosocial approach 46 61 65. An alternative view also existed, that considered the biopsychosocial model an ethically neutral scientific theory rather than an approach to care 41…”
Section: Resultsmentioning
confidence: 99%
“…These ranged from medication, surgery and physical therapy, to counselling and cognitive therapy, spiritual counselling, compassion, presence and connection. Margalit et al ’s study on the practical application of the biopsychosocial model identified that offering not only medication, but also advice on health promotion and managing emotions characterised a biopsychosocial doctor–patient encounter 46…”
Section: Resultsmentioning
confidence: 99%
“…Research emphasises the necessity for training, mentoring, and practice assessment to enhance competency in this area. [27][28][29] The observed deficiency in formal assessment raises concerns about the accuracy of clinician self-reporting, given their varying competency levels and potential overconfidence. [27,28,30,31] This concern is further compounded when tools are utilised for psychoSOCIAL assessments, as clinicians predominantly resort to psychological patient-reported outcome measures and objective assessments that would normally be considered psychological constructs such as behaviour, fear avoidance and physical literacy.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] The observed deficiency in formal assessment raises concerns about the accuracy of clinician self-reporting, given their varying competency levels and potential overconfidence. [27,28,30,31] This concern is further compounded when tools are utilised for psychoSOCIAL assessments, as clinicians predominantly resort to psychological patient-reported outcome measures and objective assessments that would normally be considered psychological constructs such as behaviour, fear avoidance and physical literacy. This suggests a potential misinterpretation of psychological and psychoSOCIAL constructs, indicating a need for further training, as highlighted by many respondents expressing a desire for specific training and selfdevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…Engel held the view that disease is the result of the interaction of biological, psychological, and social subsystems on multiple levels and highlighted the indispensable role of psychosocial factors, which explained such phenomena as the effect of living conditions on the development of the disease. The premise of the biopsychosocial approach is that the patient's disease cannot be divorced from his or her psychosocial causes, personality, and surroundings ( 2 ). Evidence has shown that social/environmental and psychological factors matter in the development of psychiatric disorders ( 3 ).…”
Section: Introductionmentioning
confidence: 99%